Managing the Non-Profit Organization / Practices and Principles - Drucker Peter F (Butterworth Heinemann, 1993)
A book aimed specifically at decision-makers and managers working in non-profit making organizations to help them apply the principles of good management to their sector. Contributors, Preface, The Mission Comes First: and Your Role as a Leader, From Mission to Performance: Effective Strategies for Marketing and Innovation and Fund Development, Managing the Performance: How to Define It; How to Measure It, People and Relationships: Your Staff and Your Board and Your Volunteers and Your Community, Developing Yourself: As a Person and as an Executive and as a Leader, Index.